PENGEMBANGAN UMKM BERBASIS TEKNOLOGI AUGMENTED REALITY UNTUK PENUNJANG PROMOSI DI DESA WISATA PENTINGSARI - Widiarti, Anastasia Rita; Pinaryanto, Kartono; Adji, Fransisca Tjandrasih (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service project aims to introduce and implement Augmented Reality (AR) technology for Micro, Small, and Medium Enterprises (MSMEs) in Pentingsari Village, Yogyakarta, enhancing their promotional capabilities. The initiative involved local MSME owners, village officials, lecturers, and students collaborating to integrate modern technology with local wisdom. The project used methods such as presentations, discussions, and AR technology demonstrations to identify unique MSME products suitable for AR enhancement and develop tailored AR applications. The results indicate high enthusiasm among participants in adopting AR technology for their product development and marketing strategies. A user survey of the developed AR application showed an overall positive response, with an average rating of 4.26 out of 5 across various aspects, including ease of installation, operation, user interface quality, and 3D model display. This project demonstrates the potential of AR technology to boost competitiveness significantly and add value to MSME products in Pentingsari Village while highlighting areas for future improvement and expansion of the AR application to support local tourism and economic development further.